High-energy magnetic excitations in CuO - Boothroyd, A; Mukherjee, A; Fulton, S; Perring, T; Eccleston, R; Mook, H; Wanklyn, B (1997)
We have used inelastic neutron scattering to study the magnetic excitations in CuO, a quasi 1-D antiferromagnet, along the chain direction, [zeta, 0, <(zeta)over bar>]. The low-energy excitations can be described adequately by linear spin wave theory, but at high energies the magnetic scattering exhibits characteristics of the spinon model.